Chemical Composition and Biological Activities of Essential Oil from Aerial Parts of Frankenia pulverulenta L. and Boerhavia elegans Choisy from Northern Oman. Issue 5 (3rd September 2021) - Rehman, Najeeb Ur; Alsabahi, Jamal Nasser; Alam, Tanveer; Rafiq, Kashif; Khan, Ajmal; Hidayatullah,; Khan, Nasir Ali; Khan, Abdul Latif; Al Ruqaishi, Houda; Al-Harrasi, Ahmed
Abstract: Evaluation of CA inhibition activity and the identification of the components of the essential oil of Frankenia pulverulenta (FPEO) and Boerhavia elegans (BEEO) were undertaken for the first time in this study. Twenty-five components were identified using Gas Chromatography/Mass Spectrometry (GC/MS) in the FPEO, representing 92.7 % of the total oil. The major components were β-caryophyllene (32.5 %), δ-cadinene (8.4 %), alloaromadendrene (7.1 %), copaene (6.9 %), and ledol (5.3 %). Similarly, the BEEO contained 13 components representing 92.9 % of the total oil with β-caryophyllene (17.1 %) and β-amyrin (13.7 %) as the major components. The results determined that the FPEO was a rich source of sesquiterpene hydrocarbons (69.8 %), while BEEO contains a higher concentration of aliphatic hydrocarbons (46.4 %). The EOS of both plants were further screened for carbonic anhydrase II (CA-II), and antimicrobial activities. Essential oil of F. pulverulenta exhibited significant CA-II activity with 101.5±2.35 % inhibition, while B. elegans essential oil presented promising bactericidal and fungicidal activities against Escherichia coli (Gramnegative bacteria) and Penicillium simplicissimumi . These results indicate that the essential oil of B. elegans can inhibit the growth of Gram-negative bacteria and fungi. In addition, FPEO significantly inhibited CA and might have the potential to be used for the treatment of CA-related diseases.